La gestión institucional y el éxito en los resultados de las pruebas estandarizadas (saber 11) en una institución educativa de Bogotá - Ballesteros Niño, Susan Bibiana; Gil Montiel, Esther Julia (Universidad Antonio Nariño, 2023)
This study shares the experience of the implementation of the improvement guide No. 34 issued by the Ministerio de Educación Nacional at a school in Bogotá city, located in the town of Suba, and the retrospective analysis of its impact on ICFES test results. The results are partially conclusive against the positive effect and correlation between the implementation process (through a proxy variable) on the average results of ICFES tests. However, the conclusions are limited due to the limited number of statistical observations.